FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP MASYARAKAT DESA PAKRAMAN BATUAN TERHADAP MITOS I GEDE MECALING - Enik Trijayanti, Ni Komang; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2017)
The myth of I Gede Mecaling has been enveloved in Batuan Pakraman Village and passed down from generation to generation. The myth told about the act of I Gede Mecaling who always hurt the people who lived in Batuan Pakraman Village. The act of I Gede Mecaling had an effect, then he was expelled from Batuan Pakraman Village. he cursed and swear that Batuan Pakraman Villagers will be affected if they cross to Nusa Penida. That myth caused the dualism attitude among the villagers in Batuan Pakraman Village, going or not going to Nusa Penida. The aim of this research is to determine the factors that affect the attitude of Batuan Pakraman Village to the myth of I Gede Mecaling. This research used qualitative descriptive reseacrh type. The data that develoved in this research used interview, observation and documentation studies method. For the selection of the informan used purposive sampling and snowball techniques. The research of this research shows that there is a dualism attitude among the villagers to the myth of I Gede Mecaling affected by expirience factor, economic factor and the value factor in the family. The myth is a communication medium because there is a message in it. Then the myth is spread oarally from generation to generation. Keywords: the myth of I Gede Mecaling, attitude formation, Batuan Pakraman Village, inheritance of caltural values.